A Brief Review of Edema-Adjusted Infarct Volume Measurement Techniques for Rodent Focal Cerebral Ischemia Models with Practical Recommendations - Nouraee, Cyrus (J Vasc Interv Neurol, 2019)
BACKGROUND: Determining cerebral infarction volume is an important part of preclinical studies to determine the benefit of potential therapies on stroke outcome. A well-known problem in determining the actual infarction volume of rodent models is the presence of edema. Because of this, algorithms must be utilized to obtain the edema-adjusted (E(A))-infarct volume. Different methods based on 2,3,5-triphenyltetrazolium hydrochloride (TTC) staining have been published describing algorithms to determine the E(A)-infarct volume. MATERIALS AND METHODS: Simulated models of infarction and corresponding swelling were employed to determine which absolute method of calculation (Lin et al., Reglodi et al., or Belayev et al.) is the most accurate in calculating the absolute E(A)-infarct volume. RESULTS: The Reglodi and Belayev methods were statistically more accurate in measuring E(A)-infarct volume than Lin’s method, p = 0.0078. Though there was no significant difference between Reglodi’s and Belayev’s methods for the E(A)-infarction volume calculation, Reglodi’s approach was closer to the ground-truth infarct volume while also being simpler and more straightforward to use. CONCLUSION: We recommend that Reglodi’s method, that is E(A)-infarct volume = infarct volume × (contralateral hemisphere/ipsilateral hemisphere), to be used in calculating E(A)-infarct volume in TTC stained rodent brains. Further, factors such as inhomogeneous infarction distribution in a given brain slice can also contribute to the error in volume calculation. Therefore, the average of the infarct area obtained from anterior and posterior views of a given slice should be used to account for the variation. Considering different factors, we have provided a summary recommendation for calculating the infarction volume.